A Mobile Technology for Hazard Management System - Kumar, Ajay; Battan, Amit Kumar; Rahul, Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The Japan is one of the countries in the world vulnerable to natural hazards because of its geographic location. Due to the advances of Internet and mobile technologies, mobile phones with Internet connection and computation capabilities are widely used now a day. The purpose of this paper is to examine the proposed hazard warning mechanism using the Location Based Service technology and a hazard information management system to rapidly distribute warning message in a short time while hazard sites are near the system users.. The disaster management system Android application known as MyDisasterDroid determines the optimum route along different geographical locations that the volunteers and rescuers need to take in order to serve the most number of people and provide maximum coverage of the area in the shortest possible time. Genetic algorithm was applied for optimization and different parameters were varied to determine the most optimum route.